(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
How to teach to think about time, historical time and its multiple components? To navigate this restlessness sinuously we rely on the image, which we understand as a representation of time. As teacher trainers in History for the secondary level and from the analysis and problematization about the use of image by the cohorts of practitioners 2018-2019, we set out to design visual narrative exercises for the development of reading and interpretation of the image. Our problems about teaching practices aim to strengthen initial training focused on historical-social education from the search for curricular justice in the contexts where future teachers begin their professional exercise and in this sense we pay attention to treatment of the image as a source-text as in invitation to expand their training including the aesthetic experience involved in that language. In this work we present first the theoretical review about time and its teaching from which we base our proposal and then develop the four exercises to design visual narratives.